Microwave-Assisted Digestion of Polyurethane Foam as an Alternative to Elution: Solid Phase Extraction of Cd(II) and Pb(II) for Their Determination in Swimming Pool Waters - Juliana Menezes de Sousa; Graziela Fregonez Baptista Cruz; Luiza Gomes dos Santos; Ricardo J. Cassella (Journal of Analytical Methods in Chemistry)
In this work, a separation/preconcentration method is proposed for the determination of Cd(II) and Pb(II) in swimming pool waters, using ammonium pyrrolidine dithiocarbamate (APDC) as a complexing agent and unloaded polyurethane foam (PUF) as a sorbent. The proposed method was optimized, and the defined optimal conditions were a pH of 7, 30 min of shaking time, 400 mg of PUF, and 0.5% (m/v) of the APDC solution. The release of Cd(II) and Pb(II) from the solid phase was achieved through the total digestion of PUF using a microwave-assisted acid approach with a 10.5 mol·L−1 HNO3 solution. The methodology was applied to four samples of swimming pool water for the determination of Cd(II) and Pb(II) using graphite furnace atomic absorption spectrometry (GF AAS). The limits of detection and quantification obtained were 0.02 and 0.06 μg·L−1 for Cd(II) and 0.5 e 1.8 μg·L−1 for Pb(II), respectively. We analyzed four samples of swimming pool waters, finding Cd concentrations between 0.22 and 1.37 μg·L−1. On the other hand, only one sample presented Pb concentration above the limit of quantification (11.4 μg·L−1). Recovery tests were performed by spiking the samples with known concentrations of the analytes, and recovery percentages between 82% and 105% were obtained.